PENGEMBANGAN PARIWISATA HALAL BERBASIS MASYARAKAT UNTUK MENINGKATKAN KESEJAHTERAAN : (Studi Kasus pada Desa Wisata Sembalun Lawang, Kecamatan Sembalun, Kabupaten Lombok Timur, Nusa Tenggara Barat) - Muh. Zaini (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2021)
Community-based halal tourism is a solution to improve community welfare and remote villages development Because some of the object distribution and tourist attractions are in rural areas. Very ironic when foreign tourist visits increase, domestic tourist spending increases and the country's foreign exchange income showing fantastic numbers. Meanwhile, on the other side of the community or local society who lives and lives around tourist attractions does not participate feel the positive impact immediately. In Sembalun Lawang Village it is now being held to develop community-based halal tourism where the community directly. Which becomes the subject as well as the tourism object itself. The aim of this study to analyze: (1), Community-based halal tourism development strategies. (2) Community participation (3), Implications for welfare. This study uses a qualitative approach type of case study. The result of the study show that: (1) Development strategy community based halal tourism in Sembalun Lawang Village is: product development or tourist tourist destination objects, promotion through the internet (social network), compile regulations that apply to all destination in accordance with sharia principles “Awik-Awik”, complement worship facilities, preparing accommodation and other infrastructure in accordance with sharia standards, improve accessibility (road widening), and improve services. (2) Community participation is: tourist managers, tour guides, producers of various creative product, traders around tourist destination objects, member of art groups become a tourist attraction and homestay lodging provider. (3) Implications for the welfare of the Sembalun Lawang community: a). According to Islam: the five welfare indicators have been fulfilled, namely: the maintenance of religion, soul, intellect, heredity, assets. b). according to BKKBN: there is increase welfare based on survey result before and after development halal tourism by using 20 indicators according to the BKKBN.